Islamic Leadership Innovation At MI AL Kamil: Between Spirituality And Professionalism - Dahari, Dahari; Hana, Syifa (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
This research aims to analyze Islamic leadership innovations in MI Al Kamil in integrating spirituality and professionalism in education management practices. The background of this research departs from the challenge of school principals in balancing administrative demands, digitization of education, and national quality standards with the strengthening of spiritual values and Islamic examples. Using a qualitative approach with a case study design, data was collected through in-depth interviews, participatory observations, and analysis of school policy documentation, then analyzed thematically using Miles and Huberman's interactive model. The results show that school principals play the role of transformational leaders who combine spiritual and professional dimensions in every aspect of leadership, including shur-based decision-making, strengthening religious work culture, and the application of innovative managerial technology. This leadership innovation not only increases the effectiveness of the school organization, but also strengthens the religious character of all school residents. Conceptually, this research offers a model of